Cegah Stunting Melalui Edukasi Kesehatan Di Masa Kehamilan Di Kelurahan Rejosari Kota Pekanbaru: Cegah Stunting Melalui Edukasi Kesehatan Di Masa Kehamilan Di Kelurahan Rejosari Kota Pekanbaru - Hetty Ismainar; Hastuti Marlina; Ani Triana (STIKes Hang Tuah Pekanbaru, 2022)
Background. Stunting is a height growth disorder. The prevalence of stunting in Riau Province based on the Indonesian Toddler Nutrition Status Survey in 2019 was 23.7% (WHO standard < 20%). The trigger for stunting is multifactorial, starting from pregnancy to 2 years of age under five. Prevention efforts are needed to reduce the prevalence of stunting. Objectives To provide health education during pregnancy through leaflets and banners for pregnant women. Methods, Health education for pregnant women in by health education media by leaflets and banners. This activity is given to mothers There were 18 pregnant women in the Rejosari village area. The understanding of the material on